Bioelectric Dysregulation in Cancer Initiation, Promotion, and Progression - Sheth, Maulee; Esfandiari, Leyla (Frontiers in Oncology, 2022)
Cancer is primarily a disease of dysregulation – both at the genetic level and at the tissue organization level. One way that tissue organization is dysregulated is by changes in the bioelectric regulation of cell signaling pathways. At the basis of bioelectricity lies the cellular membrane potential or Vmem, an intrinsic property associated with any cell. The bioelectric state of cancer cells is different from that of healthy cells, causing a disruption in the cellular signaling pathways. This disruption or dysregulation affects all three processes of carcinogenesis – initiation, promotion, and progression. Another mechanism that facilitates the homeostasis of cell signaling pathways is the production of extracellular vesicles (EVs) by cells. EVs also play a role in carcinogenesis by mediating cellular communication within the tumor microenvironment (TME). Furthermore, the production and release of EVs is altered in cancer. To this end, the change in cell electrical state and in EV production are responsible for the bioelectric dysregulation which occurs during cancer. This paper reviews the bioelectric dysregulation associated with carcinogenesis, including the TME and metastasis. We also look at the major ion channels associated with cancer and current technologies and tools used to detect and manipulate bioelectric properties of cells.